Personality Traits Contributing to Anxiety and Phobic Disorders in Psychology Students - Krupelnytska, Liudmyla; Baratiuk, Artem (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The research analyses factors of personal predisposition to anxiety and phobic disorders among psychology students. The research subject is insufficiently covered in scientific publications; therefore, it needs further study. The purpose of the research is to identify personal factors of predisposition to anxiety-phobic disorders in psychology students. The research uses Freiburg Personality Inventory, Questionnaire of the Hierarchical Structure of Actual Personal Fears; Integrative Anxiety Test; Patient Health Questionnaire (PHQ) - Panic Screening Questions. 70 students took part in the study (male/female ratio is 21/49). All of them studied at the Faculty of Psychology of Taras Shevchenko National University of Kyiv. The age of the respondents is from 18 to 22 years old, the average age is 20.00, the standard deviation is 1.47. The personal profile of psychology students is distinguished by the following characteristics. The extremes are openness (upper peak) and shyness (lower peak). The second-highest indicator is for sociability; and the third is for neuroticism. Next to the lower peak there is also an indicator of reactive aggressiveness. The research establishes gender differences in the manifestation of neuroticism and reactive aggressiveness of psychology students, the correlation of current fears, anxiety, and the tendency to panic attacks with personality characteristics. It builds prognostic models of the influence of personal traits on the tendency to manifest current fears, situational and personal anxiety, and panic attacks. In descending order of influence: phobic symptoms are influenced by anxious assessment of prospects, shyness, emotional lability; personal anxiety is influenced by depression, neuroticism, spontaneous aggressiveness; situational anxiety is influenced by depression, current fears and introversion; tendency to panic attacks is influenced by neuroticism.